PENGARUH PRODUK, HARGA, LOKASI, DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN MINUMAN TEH HIJAU (STUDI KASUS PADA DAPUR TEA IJO CABANG GUNUNG GANGSIR, KABUPATEN PASURUAN) - Rachmah Tri Inayah; Septine Brillyantina; Sekar Ayu Wulandari; Rahman Humaidi (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of the home-based industry in East Java shows an increasingly dynamic competition alongside the rising public interest in trendy contemporary beverages. One highly sought-after beverage is green tea, owing to its image as a practical, refreshing drink that aligns with modern lifestyles. Among the tea-based beverage businesses developing in Pasuruan Regency is Dapur Tea Ijo, specifically the Gunung Gangsir Branch. This business was selected as the research object due to its strategic location near community activities, despite still facing unstable daily sales fluctuations. This study focuses on analyzing the influence of product, price, location, and consumer attitude variables on purchasing decisions for green tea beverages, both simultaneously and partially, as well as identifying the most dominant variable. The research method employed is associative quantitative with a survey approach. The sampling technique was conducted via accidental sampling, involving a total of 50 respondents. Data analysis used multiple linear regression, instrument testing (validity and reliability), classical assumption testing, and hypothesis testing (F-test and t-test) processed through IBM SPSS 16 software. The results indicated that, simultaneously, all four variables have a significant effect on purchasing decisions. Partially, however, only the product and price variables proved to have a positive and significant impact, whereas the location and consumer attitude variables did not show a significant effect. The price variable was found to be the most dominant factor influencing purchasing decisions for green tea beverages at Dapur Tea Ijo, Gunung Gangsir Branch.